2014
DOI: 10.1016/j.ygeno.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in lipogenic genes and milk fatty acid composition in Holstein dairy cattle

Abstract: Changing bovine milk fatty acid (FA) composition through selection can decrease saturated FA (SFA) consumption, improve human health and provide a means for manipulating processing properties of milk. Our study determined associations between milk FA composition and genes from triacylglycerol (TAG) biosynthesis pathway. The GC dinucleotide allele of diacylglycerol O-acyltransferase 1:g.10433-10434AA >GC was associated with lower palmitic acid (16:0) concentration but higher oleic (18:1 cis-9), linoleic (18:2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 54 publications
3
14
0
Order By: Relevance
“…Results obtained in studies on human and animal models identified and characterized C16:1 cis-9 as a novel lipokine or lipid hormone (German, 2011). Nafikov et al (2014) did not observe any significant association between LPIN1 haplotypes and the milk fatty acid composition in Holstein cows.…”
Section: Lipinmentioning
confidence: 68%
See 3 more Smart Citations
“…Results obtained in studies on human and animal models identified and characterized C16:1 cis-9 as a novel lipokine or lipid hormone (German, 2011). Nafikov et al (2014) did not observe any significant association between LPIN1 haplotypes and the milk fatty acid composition in Holstein cows.…”
Section: Lipinmentioning
confidence: 68%
“…Several prior studies have taken the approach of performing association analyses between candidate genes and the milk fatty acid profile, but these studies considered relatively few genes and fatty acid traits (e.g., Rincon et al, 2012;Marchitelli et al, 2013;Nafikov et al, 2014). Moreover, to our knowledge, only one previ-ous study reported association analyses with the milk fatty acid profile of the Brown Swiss breed (Strillacci et al, 2014).…”
Section: Associations Of Candidate Genes With Milk Fatty Acid Profilementioning
confidence: 99%
See 2 more Smart Citations
“…This supports the contention that LPIN1 is having an effect on milk traits in two bovine species, and is consistent with yaks and cattle being closely related to each other. However, this does need to be balanced against the findings of Nafikov et al (2014), who found no association between a SNP in the 5 ′ UTR of Holstein cattle and milk traits.…”
mentioning
confidence: 91%